Information seeking behaviour of academic researchers in the field of information technology - Rosidah Awang. (2009)
This study explores the information seeking behaviour of ten academic researchers of the Information Communication Institute of Singapore in June 1995. The main objectives of this dissertation are to analyse the information needs of this group, their information seeking patterns, problems encountered and how Internet affects their information seeking behaviour. The data was gathered by means of face-to-face interview. Three theoretical models of information seeking behaviour are also discussed to provide background knowledge of the information seeking process. Results of this study are analysed and implications for the library services in Singapore are then outlined.